Impact of Light Soaking on p‐Type Boron‐ and Indium‐Doped Passivated Emitter and Rear Solar Cells on Czochralski‐Grown Silicon. Issue 6 (1st April 2019) - Balaji, Nagarajan; Shanmugam, Vinodh; Raj, Samuel; Ali, Jaffar Moideen Yacob; Aguilar, Ma Luisa O.; Garcia, Ison Jeffrey; Rodriguez, John; Aberle, Armin; Duttagupta, Shubham
Abstract : Solar cells fabricated on boron‐doped Czochralski‐grown silicon (Cz‐Si) wafers are known to suffer from light‐induced degradation (LID). In this work, the effect of light soaking on passivated emitter and rear (PERC) solar cells fabricated on both indium (In)‐doped Cz‐Si and boron (B)‐doped Cz‐Si wafers are investigated. Efficiencies up to 20.7% and 21.2% are obtained on In‐doped and B‐doped Si wafers, respectively. Though the initial conversion efficiency is lower with In‐doped Si wafers, these cells show no LID after light soaking (1.0 Sun illumination at 25 °C for 85 h). In contrast, cell efficiencies dropped significantly for B‐doped Si wafers, by 0.8%. Abstract : Impact of light soaking on indium ‐and boron ‐doped p ‐type Czochralski silicon wafers on passivated emitter and rear solar cells are studied. Efficiencies up to 20.7% and 21.2% are obtained on In‐doped and B‐doped Si wafers, respectively. In‐doped Si wafers show no light‐induced degradation after light soaking (1.0 Sun illumination at 25 °C for 85 h).